Caracterización de capas delgadas de tungsteno obtenidas mediante High power impulse magnetron sputtering (HiPIMS) - James-Petretti, Stephen (My University, 2019)
High Power Impulse Magnetron Sputtering (HiPIMS) is a novel thin film processing method to achieve include higher density, better substrate adhesion, and smoother surfaces compared to conventional DC sputtering (DCms). The Max-Planck Institute for Plasma Physics is seeking to enable a HiPIMS device to maintain its leading position in scientific research in advanced coatings. In this work, the first results of W coatings on Si and W obtained with a new HiPIMS power source, P = 200 W, tpulse = 10 μs and f = 2000 Hz, were evaluated. Physical properties such as microstructure, density, roughness, and impurity content were compared with films obtained via DCms under the similar processing conditions. It was found that the HiPIMS method achieves a ~10% increase in density, and eliminates the β-W phase in W over Si films, compared to films obtained with the conventional DCms method. The addition of a bias voltage Vb = -120 V decreased the root mean square (RMS) of the roughness in W films over W substrate obtained by both DCms and HiPIMS
Proyecto de Graduación (Bachillerato en Ingeniería de Materiales) Instituto Tecnológico de Costa Rica, Escuela de Ciencia e Ingeniería de los Materiales, 2019.
Keywords: Procedimientos; Capas; Recubrimientos; Ciencia de los materiales; Research Subject Categories::TECHNOLOGY::Materials science::Surface engineering